Al/P-Si/Coumarin:TiO2/Al Organic-Inorganic Hybrid Photodiodes: Investigation of Electrical and Structural Properties - Aslan, Fehmi; Esen, Hikmet; Yakuphanoğlu, Fahrettin (Springer, 2020)
In this study, Coumarin:TiO2 thin films synthesized by sol-gel method in different coumarin weight ratios were formed by drop casting technique on p-Si. The structural and electrical properties of the synthesized Coumarin:TiO2 thin films were investigated. Nanostructures of synthesized TiO2 were well crystallized at higher Ti concentrations. In addition, photodiode properties of organic-inorganic hybrid Al/p-Si/Coumarin:TiO2/Al samples prepared at varying coumarin concentrations were studied with current-voltage (I-V) characteristics under different illuminations. It was seen that all produced photodiodes had excellent rectifier properties due to the calculated good rectification rates. Also, it was stated that the photocurrents of all produced devices under dark conditions were smaller than those under illumination conditions. Among all the devices fabricated, the highest photosensitivity was observed for photodiode produced with 1% coumarin at under illumination 100 mW/cm(2). Electronic parameters such as ideality factor (n) and barrier height (phi(b)) were found in ranges 3.1-11.4 and 0.460-0.473 eV, respectively. The temporary photocurrent-time characteristic of the diodes confirmed that the produced devices were light sensitive. Electrical behaviors of the fabricated devices were investigated by means of capacity-voltage (C-V) and conductivity-voltage (G-V) measurements at different frequencies. It was determined that capacity and conductivity decreased and increased, respectively by increasing frequency. This behavior is due to the presence of the interface states of the produced samples. Structural and electrical characterization results showed that all fabricated devices could be operated as optical sensors or photodiodes in optoelectronic fields.
Keywords: Photodiode; Thin films; Structural and photoresponse analysis; Organic-inorganic based devices